The Abundance of Gastropoda in Bonebula Beach Central Banawa Sub-District and The Utilization as Learning Media - Safaat Safaat; Musdalifah Nurdin; Syech Zainal; Abd. Rauf (CV. Dharma Samakta Edukhatulistiwa, 2024)
The objective of this study is to describe the abundance of gastropods in the marine waters of Bonebula Beach, Banawa Tengah Subdistrict, and to utilise the findings as a learning resource in the form of electronic pocket books. The research methodology employed is descriptive quantitative research, with the location determined through purposive sampling, resulting in the designation of three observation stations. Station 1 is situated within the seagrass ecosystem, Station 2 within the mangrove ecosystem, and Station 3 within the coral ecosystem. The sampling was conducted using a free collection method. The findings revealed the presence of 19 species of gastropods belonging to 13 families and six orders. The abundance of gastropods on Bonebula Beach is classified as moderate, representing 18.33% of the total population. The percentage of content experts, design experts and media experts is 85%, 85.33% and 84.29%, respectively, with an average feasibility rating of 84.87%. This indicates that the electronic pocket book medium is highly feasible for use.